Giant Liver Abscess with Atypical Clinical Presentation: Case Report. - Flores-López , Alejandro Alberto; Gómez-Salazar, Adriana Guadalupe; Chacón-Pacho , Ricardo Efraín; Espinosa-Rosales, Alicia Valeria; Falcón-Cancino, Luis Arturo; Agustín-Martínez, Luis Alejandro; Cáceres-Moreno, Cristóbal Aldair; Villalobos-Rodríguez, Alejandro Lenin; Padrón-Arredondo , Guillermo (British Journal of Healthcare and Medical Research, 2023)
Background. Amebiasis is caused by the protozoan Entamoeba histolytica. This parasite exists in 2 stages: a cyst, which is the infective form, and a trophozoite stage, which is the form that causes invasive disease. Globally, around 500 million people are infected annually. Clinical case. A 73-year-old female upon arrival at the emergency department with laboratories without alterations. Relevant ultrasound reports chronic gallbladder lithiasis not exacerbated and significant gastric distension. A liver abscess is suspected, for which an assessment is requested by the interventional radiology service for percutaneous drainage, commenting that it is not a candidate because, due to ultrasonographic characteristics in the scan before the puncture, they suspect a hydatid cyst and the puncture site is proximal to the blood vessels. It is programming exploratory laparotomy with the following findings: enlarged liver, firm adhesions to the posterior wall of the stomach and the diaphragm, a hepatic abscess is drained, obtaining 2000 mL of thick purulent material, it is marsupialized and culture is taken with a negative report to bacterial development at 48 hours. Discussion. It is a 44-year-old male with intense abdominal pain in the right upper quadrant, generalized jaundice, tachycardia, and fever; the hepatic edge is palpated 5 cm below the costal margin, positive Murphy’s sign. Laboratory studies: direct hyperbilirubinemia, elevation of alkaline phosphatase and transaminases, leukocytosis, a negative viral panel for hepatitis, and positive antibodies for Entamoeba histolytica. The abdominal computed tomography showed a hypodense lesion measuring 15 by 12.1 cm in the right hepatic lobe.